If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = 5(2x + 1) Reorder the terms: 3(-1 + 2x) = 5(2x + 1) (-1 * 3 + 2x * 3) = 5(2x + 1) (-3 + 6x) = 5(2x + 1) Reorder the terms: -3 + 6x = 5(1 + 2x) -3 + 6x = (1 * 5 + 2x * 5) -3 + 6x = (5 + 10x) Solving -3 + 6x = 5 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -3 + 6x + -10x = 5 + 10x + -10x Combine like terms: 6x + -10x = -4x -3 + -4x = 5 + 10x + -10x Combine like terms: 10x + -10x = 0 -3 + -4x = 5 + 0 -3 + -4x = 5 Add '3' to each side of the equation. -3 + 3 + -4x = 5 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = 5 + 3 -4x = 5 + 3 Combine like terms: 5 + 3 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 3(3-2m)=5m-35 | | r^2=6 | | 124=76x+32x | | -9y+13=20-7y | | 30/5+4x=34 | | -5(3t-5)+7t=6t-8 | | a=zt+z | | 2x^3+4=3x^5-2 | | 10n+7+5n=8n-21 | | 10n+7+5n=8n-521 | | 2z+2iz-5i=0 | | 2z+2iz-5=0 | | 4(3z-2)-3(z-2)=61 | | 15y^2-12y=3y | | 10x/3+3=-8 | | m^2-12m+5=0 | | 4/3(1077.02) | | 2[w-(4w+12)+2]=2(w+10) | | 3a^2b-12ab^2= | | 6x+4-6x=7 | | 80x-5x^2=140 | | 80x-fx^2=140 | | v=4/3(3.14)343 | | 8x+2=12x-30 | | 3-2x=3-2x | | -4-x/9=-8 | | 7(2x+3)=4x+1 | | 6(3-2x)=6-12x | | 16=-8x-8 | | 7x-2+3x=-8+10x | | 5x+1=5x+3 | | (9x+8)+9x= |